Companies and human rights - Tapia-Gutiérrez, Asier (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The responsibility of transnational corporations on human rights have been in the centre of debate. Clearly, the room for maneuver of the multinationals have altered the own State sovereignty, and therefo re it is necessary to control the excesses. However, the proposed mechanisms in the international regime, are far from being really efficient and seems rather protect deviations, so it is necessary to work hard in limiting the actions of these companies, which have caused severe environmental damage